Minimally manipulated murine regulatory T cells purified by reversible Fab Multimers are potent suppressors for adoptive T-cell therapy - Mohr, Fabian; Fischer, Julius Clemens; Nikolaus, Marc; Stemberger, Christian; Dreher, Stefan; Verschoor, Admar; Haas, Tobias; Poeck, Hendrik; Busch, Dirk H. (European Journal of Immunology, 2017)
The transfer of regulatory T cells, either freshly isolated, or modified, represents a promising therapeutic approach to dampen misdirected immune responses, like autoimmune diseases, chronic inflammatory syndromes and graft versus host disease. Clinical isolation of highly pure regulatory T cell (Treg) populations is still challenging and labeling reagents can influence their viability and functionality, potentially altering the potency of isolated Treg cell products. Here we show that reversible Fab multimer-based Treg purification can prevent conventional antibody label-induced interferences in vitro and in vivo. Remaining isolation reagents negatively interfere with Treg engraftment efficacy in C57BL/6 wild-type mice due to Fcγ-receptor- as well as IL-2 receptor-mediated mechanisms. Using a preclinical model for acute GvHD, we further show that purified ‘label-freed’ Tregs are protective at substantially lower cell numbers as compared to conventional nonreversible antibody staining, translating into significantly improved survival of mice treated with minimally manipulated Tregs. These findings have important clinical relevance for future Treg-based cell therapies.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Adoptive T cell transfer; Graft-versus-host-disease; Regulatory T cells; Reversible multimer staining; T-cell therapy